Global health education experience of a multidisciplinary curriculum at Rouen school of medicine, France (One Health & Risk Management, 2021)
Introduction. The interest in Global Health (HG) as an academic discipline has increased in the last decade. The Rouen School of Medicine is one of the first to offer a GH curriculum in France. The objective was to identify the characteristics and profile of students involved in a GH curriculum. Material and methods. In 2016 and 2017, a cross-sectional study was conducted, including enrolled in the GH course: 3rd and 4th year in medicine, midwifes studies and pharmacy. Based on self-questionnaire, data collected were motivations for health studies, investment in humanitarian associations, opinions about the GH topics. Results. A total of 422 students were included; 122 students attended to GH cursus (GH+) and 300 in control group (GH-). The students of the GH+ group were more likely to get involved in a humanitarian association (22.3% versus 6.7%, p